Pengaruh Budaya Terhadap Efektivitas Proses Pembelajaran - Ufi Rumefi; Khamdan Suriyok; Arif Syaifudin (Proceedings Series of Educational Studies, 2023)
In an educational institution, educational culture is important in shaping individual character inaccordance with their respective roles and functions in order to achieve the goals of educationalinstitutions, This study aims to analyze the influence of educational culture consisting of discipline,norms and beliefs on learning effectiveness. Data collection was carried out through thedistribution of questionnaires to 52 students at Smart Education Beji Pasuruan as respondents,Testing in this study was assisted by a data analysis test tool, namely SPSS version 16. Based on theresults of the study, it is known that the variables of discipline (X1), norms (X2) and trust (X3)simultaneously have a significant effect on the effectiveness of the learning process, partial testingof all dependent variables has a positive and significant effect on the effectiveness of the learningprocess. so that it can be concluded that the culture of education both partially and simultaneouslyaffects the effectiveness of the learning process and more specifically in this study the disciplinevariable has the most dominant effect on the effectiveness of the learning process in SmartEducation educational institutions.